Chromosome-level genome assembly for giant panda provides novel insights into Carnivora chromosome evolution - Fan, Huizhong; Wu, Qi; Wei, Fuwen; Yang, Fengtang; Ng, Bee Ling; Hu, Yibo (Genome Biology, 2019)
Chromosome evolution is an important driver of speciation and species evolution. Previous studies have detected chromosome rearrangement events among different Carnivora species using chromosome painting strategies. However, few of these studies have focused on chromosome evolution at a nucleotide resolution due to the limited availability of chromosome-level Carnivora genomes. Although the de novo genome assembly of the giant panda is available, current short read-based assemblies are limited to moderately sized scaffolds, making the study of chromosome evolution difficult. Here, we present a chromosome-level giant panda draft genome with a total size of 2.29 Gb. Based on the giant panda genome and published chromosome-level dog and cat genomes, we conduct six large-scale pairwise synteny alignments and identify evolutionary breakpoint regions. Interestingly, gene functional enrichment analysis shows that for all of the three Carnivora genomes, some genes located in evolutionary breakpoint regions are significantly enriched in pathways or terms related to sensory perception of smell. In addition, we find that the sweet receptor gene TAS1R2, which has been proven to be a pseudogene in the cat genome, is located in an evolutionary breakpoint region of the giant panda, suggesting that interchromosomal rearrangement may play a role in the cat TAS1R2 pseudogenization. We show that the combined strategies employed in this study can be used to generate efficient chromosome-level genome assemblies. Moreover, our comparative genomics analyses provide novel insights into Carnivora chromosome evolution, linking chromosome evolution to functional gene evolution.